Analisis Kepuasan Pengguna Sistem Informasi Tata Usaha (SITU) Pada Universitas Negeri Gorontalo - Machmud, Rizan (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2014)
The research aims to find out the partialinfluence (system quality and information quality) of users’ satisfaction on administration information system.